The organization of research work of students - a pledge of the intellectual creativity of future specialists (Pedagogy of Higher and Secondary Education, 2012)
Bayrak L. The organization of research work of students - a pledge of the intellectual creativity of future specialists.Annotation is a research work of students in Mining technical school SHEE KNU, which is considered as the most effective and active constituent of the educational technology. Under the certain circumstances it permits to create the researcher qualities of students, skills for quick and effective implementation of those scientific and technical achievements, that can provide the increasing of productivity and labour culture. The organizational structure of students’ research work in Mining technical school SHEE KNU is shown there.
Keywords: research work; production tasks; actuality; innovation; organizational structure